Statin Therapy and the Risk of Rhabdomyolysis in Physically Active Individuals: Implications for Sports Medicine - Ceryn, Julia; Kopeć, Katarzyna; Marchwińska-Pancer , Aleksandra; Michalak, Paweł; Bolesta-Okuniewska , Emilia; Radziwon , Maja; Pastuszek , Oskar; Borowski, Konrad; Wicher, Anna (Quality in Sport, 2026)
Background. Statins are widely prescribed for cardiovascular prevention and generally have a favorable safety profile. However, skeletal muscle adverse effects occur and, rarely, may progress to rhabdomyolysis, which can lead to acute kidney injury and death. Aim. To summarize current evidence on statin-induced rhabdomyolysis, including epidemiology, mechanisms, risk factors, and clinical management, with emphasis on physically active individuals and sports medicine practice. Material and methods. Narrative review of clinical trials, observational studies, pharmacovigilance analyses, and case reports addressing statin-associated rhabdomyolysis, exercise-related risk, drug–drug interactions, and patient susceptibility factors. Results. Rhabdomyolysis is rare in randomized trials but appears more frequently in real-world settings, especially with high-intensity statin regimens, interacting medications (e.g., CYP3A4 inhibitors), renal/hepatic dysfunction, and genetic predisposition. Strenuous or unaccustomed exercise may act synergistically with statin-related myotoxicity, complicating diagnosis in athletes due to overlap with post-exercise soreness and physiological CK elevations. Conclusions. Although uncommon, statin-induced rhabdomyolysis is clinically important. Individualized risk assessment, patient education, early symptom recognition, prompt statin discontinuation when suspected, and supportive management are essential, particularly in physically active populations.